Phytochemical screening and natural killer cells immunomodulation effects of pereskia bleo leaves extract on cervical cancer cells - Salleh, Siti Farhanah Mohd (2020)
Pereskia bleo is a leafy and edible plant, locally known as 'Pokok Jarum Tujuh Bilah" which has anti-cancer properties. This study purposed to elucidate the underlying mechanism of this plant as anti-cancer in inducing cell death as well as to evaluate its immunostimulatory effects on Natural Killer cells (NK cells) as a potential additional anti-cancer effect. In this study, the leaves of P. bleo were extracted using propenyl) and hexadecanoic acid. PBEA exhibited the lowest IC50 value (14.37 ± 8.40 μg/ml) indicated the strongest cytotoxic effect selectively on cervical cancer cells (HeLa). The cell cycle analysis showed inhibition of cell proliferation at G0/G1 phase in PBEA treated HeLa cells as evidenced by a significant accumulation of the cells at this phase (P<0.05). Morphological examination on PBEA treated HeLa cell showed the presence of fragmented nuclei and condensation of chromatin while apoptosis was detected in the Annexin V/PI assay. Analysis of apoptotic proteins revealed a significant upregulation of pro-apoptotic proteins (Bax, p53 and caspase-3) while downregulation of anti-apoptotic protein Bcl-2 (P<0.05) in PBEA treated HeLa cells. Meanwhile, NK cells proliferation at 24 h was found significantly increased compared to 48 h and 72 h of PBEA treatment (P<0.05). Apoptosis of HeLa cells was markedly increased in PBEA treated NK cells from cancer patients. This extract also enhanced granzyme B and IFN-